2017
DOI: 10.1007/s00402-017-2646-6
|View full text |Cite
|
Sign up to set email alerts
|

Complications during hospitalization and risk factors in elderly patients with hip fracture following integrated orthogeriatric treatment

Abstract: After integrated orthogeriatric treatment, a complicated course was seen in 49.6% of the patients with a hip fracture. The in-hospital mortality rate was 3.8%. Important risk factors for a complicated course were increasing age, poor medical condition and delirium risk VMS Frailty score. Awareness of risk factors that affect the course during admission can be useful in optimizing care and outcomes. In the search for possible areas for improvement in care, targeted preventive measures to mitigate delirium, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
59
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 21 publications
2
59
0
4
Order By: Relevance
“…The yearly incidences of pneumonia or UTIs in our study are lower compared to previous studies (with exception of UTI in one study (8) ), evaluating the risk after hip fracture surgery. (8)(9)(10)(11) However, these studies have several limitations; including only descriptive analysis and small study populations, (8)(9)(10)(11) measuring outcome as patient-reported, (11) or restricted to patients treated at a single institution or a selected university hospital. (8,9,11) We extended the knowledge by including community-based infections, evaluating trends over time, and considered death as competing risk to minimize potential bias.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The yearly incidences of pneumonia or UTIs in our study are lower compared to previous studies (with exception of UTI in one study (8) ), evaluating the risk after hip fracture surgery. (8)(9)(10)(11) However, these studies have several limitations; including only descriptive analysis and small study populations, (8)(9)(10)(11) measuring outcome as patient-reported, (11) or restricted to patients treated at a single institution or a selected university hospital. (8,9,11) We extended the knowledge by including community-based infections, evaluating trends over time, and considered death as competing risk to minimize potential bias.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…About 9% to 11% of hip fracture patients have been reported to develop hospital‐acquired pneumonia and 4% to 17.9% to develop urinary tract infection, within a varying follow‐up time window spanning from during admission to 6 months of follow‐up. Pneumonia is a leading cause of death among hip fracture patients, and is associated with an excess mortality risk among hip fracture patients .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When these are recognised and tackled in an early admission stage, preventive multidisciplinary and nursing interventions may reduce adverse frailty outcomes (i.e. mortality) (Folbert et al, 2017;Pepersack, 2008). Screening tools may facilitate detecting frail patients, perhaps even better than quick clinical bedside observations (Hii, Lainchbury, & Bridgman, 2015), and may improve awareness on frailty among health professionals (Ament, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Geriatricians will play a key role in enhancing care for older persons with hip fractures (37)(38)(39)(40), trauma (41,42), delirium, utilizing Delirium Intensive Care Units and other techniques (43)(44)(45)(46), and stroke patients (47,48). Working with dietitians they will have a specific role on preventing and treating undernutrition and cachexia in the hospital setting (49)(50)(51)(52)(53).…”
mentioning
confidence: 99%